Prefesionalización y educación tecnológica - Betancourt Uscátegui, Alvaro (Ingeniería, 1999)
A central problem in the Colombian education is the absence of a coherent educational system. The primary education is not sufficiently connected with the high school and this one with the university studies (technical, technological and university). It causes more the last one, that it has no clarity on the different levels specially in the area of the engineering, purpose of this paper.